2015
DOI: 10.1039/c5nr05586e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid flame synthesis of internal Mo6+ doped TiO2 nanocrystals in situ decorated with highly dispersed MoO3 clusters for lithium ion storage

Abstract: The rational design of nanoheterostructured materials has attracted much attention because of its importance for developing highly efficient LIBs. Herein, we have demonstrated that internal Mo(6+) doped TiO2 nanocrystals in situ decorated with highly dispersed MoO3 clusters have been realized by a facile and rapid flame spray pyrolysis route for electrochemical energy storage. In such intriguing nanostructures, internal Mo(6+) doping can improve the conductivity of electrode materials and facilitate rapid Li(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…In order to induce visible light activity into normally purely UV‐active TiO 2 , thus enabling its activation for photocatalytic processes also by visible light, a number of TiO 2 ‐based hybridization strategies were proposed, especially transition metal doping . The effect of doping on the activity depends on many factors, for example, the method of doping, and the type and the concentration of dopant .…”
Section: Introductionmentioning
confidence: 99%
“…In order to induce visible light activity into normally purely UV‐active TiO 2 , thus enabling its activation for photocatalytic processes also by visible light, a number of TiO 2 ‐based hybridization strategies were proposed, especially transition metal doping . The effect of doping on the activity depends on many factors, for example, the method of doping, and the type and the concentration of dopant .…”
Section: Introductionmentioning
confidence: 99%
“…For the Ti 2p region (Figure b), the peaks of Ti 2p 3/2 and Ti 2p 1/2 are present at 458.7 and 464.5 eV, respectively, and the 5.8 eV peak separation of which reveals that the titanium(IV) atoms are bonded stoichiometrically to oxygen atoms . As displayed by Figure c, the peak centered at 530.44 eV is assigned to the lattice oxygen of Mo−O and Ti−O bonds in molybdenum trioxide and titania, respectively; and the peaks at 531.83 and 533.28 eV are attributed to the surface hydroxyl group of Ti−OH and the chemisorbed water molecules, respectively . These results confirm that the MoO 3 /TiO 2 composite is formed, which agrees well with the HR‐TEM results discussed above.…”
Section: Resultsmentioning
confidence: 99%
“…These results confirm that the MoO 3 /TiO 2 composite is formed, which agrees well with the HR‐TEM results discussed above. Compared with the O 1s spectrum of the control sample of MoO 3 flakes (Figure S7 in the Supporting Information), the peak of lattice oxygen (530.44 eV) observed in the MoO 3 ‐76 %‐TiO 2 composite showed a negative shift of 0.26 eV in the binding energy, which was caused by electron transport from Ti 4+ to Mo 6+ due to the stronger electronegativity of molybdenum than that of titanium …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But its lower electrical conductivity limits its further application in the large‐scale energy storage fields. It has been found that the compounds formed by coating or doping with additives in TiO 2 could effectively improve the electrochemical performance of TiO 2 , such as Fe 3 O 4 /TiO 2 hollow spheres, Ag or Au nanoparticle‐embedded TiO 2 nanofibers, Zn‐doped mesoporous TiO 2 , Sn‐doped carbon‐coated TiO 2 spheres, and Mo 6+ ‐doped TiO 2 . Among these additives, content of the silicon in nature is abundant, and its theoretical capacity attains 4200 mAh/g.…”
Section: Introductionmentioning
confidence: 99%